Kemungkinan Terjadinya Slagging Dan Kerugian Efisiensi Akibat Penggunaan Low Rank Coal Pada Boiler PLTU Suralaya Unit 8 - Prayudi Prayudi; Ik Agla (Sekolah Tinggi Teknik - PLN, 2013)
Design a coal-fired power plant is made based on the type and specifications of the coal that will be used. In other words, the power plant can only use one type of coal. Suralaya unit 8 uses coal from Kalimantan to the type of low rank coal and calorific value of 4200 kcal / kg. The low rank coal when burned will produce enough ash to be a pretty big slagging potential. This thesis discusses any loss suffered in the event of slagging. And its effects on the efficiency of the boiler, as well as the way in which the Suralaya unit 8 in troubleshooting the slagging.